Ideal hourglass nodal loop state in the monolayer lithium hydrosulfide - Fang, Fang; Yu, Yanwei; Zhang, Li; Li, Yang (Frontiers in Chemistry, 2024)
In recent years, the exploration of topological states within two-dimensional materials has emerged as a compelling focus, complementing their threedimensional counterparts. Through theoretical calculations, we unveil the exceptional topological state in the monolayer lithium hydrosulfide, where an ideal hourglass nodal loop is identified. Notably, this nodal loop is characterized by only four bands, representing the simplest configuration for realizing hourglass dispersion. We provide detailed symmetry arguments alongside model calculations to elucidate the formation mechanism of the nodal loop and its corresponding hourglass dispersion. Moreover, the associated edge states are not only well-separated from the bulk band projection but also persist consistently throughout the Brillouin zone. Due to the lightweight constitutive elements of this material, both the hourglass dispersion and the edge states remain robust even in the presence of spin-orbit coupling. To enhance its practical applicability, we have evaluated various mechanical parameters, analyzing their anisotropic behaviors. Furthermore, we examined the material's response to strain conditions under both compressive and tensile stress, uncovering distinct variations in energy, size, and the hourglass dispersion of the nodal loop. Overall, the 2 hourglass nodal loop state explored in this study, along with the proposed material candidate, provides a strong foundation for future experimental investigations. This research potentially paves the way for significant advancements within this emerging field.